A Debate about Women in Iliad 20.251-55? The Evidence of Four Scholia - Mayhew, Robert (Classica et Mediaevalia, 2021)
In Iliad 20, Aeneas and Achilles trade insults, and at one point (251-55) Aeneas says that they are acting like women (ὥς τε γυναῖκας). Four Iliad-scholia provide evidence that the authenticity of this passage was disputed, and one of these scholia refers to a comment about women in Aristotle’s Historia animalium, in order to explain or defend these verses. This note highlights these scholia and this dispute, which have not received sufficient scholarly attention, while illustrating one of the uses ancient Ho- meric scholars made of the Historia animalium.